Empowerment of Miftahunnajah Islamic Boarding School Students in Sleman Yogyakarta with the Integrated Green Farming System - Fitri, Noor; Pramono, Wahyudi Budi; Maulidiyah, Riskiyatul; Burhanuddin, Burhanuddin (Jurnal Abdimas, 2023)
This service activity is the result of a study of the uniqueness of the electrical and chemical engineering field applied to agriculture and fisheries. The application of the system is called Integrated Green Farming (IGF). IGF is an integrated hydroponic fishery and farming system that utilizes fish waste residue as a nutritional supplement for hydroponic plants. Hydroponic plants are essential plants that can be used for essential oil production. The system is supported by a solar power generation system to work without needing an external electrical energy supply. This system is implemented in Islamic boarding school management partners to provide students with entrepreneurial skills. The stages of the activity consist of preparation, implementation and evaluation. The preparatory phase includes delivering materials related to the system to be built and preparing materials needed to implement activities. At the same time, the implementation stage is creating and maintaining a system involving students. Meanwhile, in the evaluation stage, monitoring of system performance and the success of essential plant and fish projects is carried out after three months. The result of this community service activity is the Integrated Green Farming (IGF) system which is implemented at the Miftahunnajah Modern Islamic Boarding School (PPM) partners. The IGF system is functioning properly, the essential plant of mint leaves is thriving, and the catfish is ready to be harvested. The developed IGF system can be applied to other communities/Islamic boarding schools because it is relatively easy to implement and maintain.